The Influence of The PjBL vs Direct Instructional Model and Initial Ability on Knowledge and Skills - Sunah Sunah; Rufii Rufii; Ujang Rohman (Eduvest - Journal of Universal Studies, 2024)
The objectives of this development are to (1) To examine differences Model Project Based Learning (PjBL) and initial ability to learn knowledge and skills in economics subjects. This experimental research was carried out using a Factorial 2 x 2 with multivariant analysis technique (Anonymous). The subjects in this study are grade XI students consisting of four classes with 130 students SMA Negeri 1 Ketapang. The subjects that were the focus of the experiment were taken at classical randomization, namely four classes of ABCD from SMA Negeri 1 Ketapang. The hypothesis of this study was tested using a statistical test analisis multivariant (Anonymous). The results of the calculation show that: (1) There is a difference Knowledge students who use model PjBL and methods direct instruction, (2) There is a difference Knowledge students who have Initial abilities tall and who has Initial abilities low, (3) There is an interaction between model PjBL and methods direct instruction with Initial abilities against Knowledge, (4) There is a difference Skills students who use model PjBL and methods direct instruction, (5) There is a difference Skills students who have Initial abilities tall and who has Initial abilities low, (6) There is an interaction between model PjBL and methods direct instruction with Initial abilities against Skills in grade XI students SMA Negeri 1 Ketapang. Based on the results of the study, it was concluded that by using model PjBL and Initial abilities can improve Knowledge and Skills students in Economics class XI SMA Negeri 1 Ketapang.